Corporate sustainable development: A historical rescue and a current debate (Research, Society and Development, 2023)
Currently, the debate involving environmental issues has become broader and internationalized, being discussed in several international conferences since the 1970s. Sustainable development can be reflected by several economic, social and environmental factors that are closely interconnected with each other and with the added dimension of time, which emphasizes the long-term perspective of various factors. Due to their central role in human activities and development, companies must play an important role in achieving sustainability goals. The main objective of this article is to list the main historical events on the care of the environmental issue, showing how sustainability gained space in the political, business and social spheres. Literature review and access to public documents were used as a methodology. This article intends to answer the following question: what are the most important events that resulted in the generation of concern about sustainability?